Solution‐Processed Graphene Composite Films as Freestanding Platinum‐Free Counter Electrodes for Bendable Dye Sensitized Solar Cells. Issue 1 (28th October 2015) - Zhou, Qinqin; Chen, Shan; Zhang, Miao; Wang, Liduo; Li, Yingru; Shi, Gaoquan
Abstract: Sulfuric acid‐treated poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate)/less‐defective reduced graphene oxide (ST‐PEDOT:PSS/L‐rGO) composite films were prepared via a solution‐processing route and used as the counter electrodes of dye sensitized solar cells (DSSCs). These platinum (Pt)‐ and transparent conductive oxide (TCO)‐free counter electrodes exhibited strong catalytic activity and excellent flexibility, showing no obvious change in their sheet resistances after 10000 cycles of bending. The integrated quasi‐solid‐state DSSC device with a TiO2 nanotube/Ti mesh photoanode and a ST‐PEDOT:PSS/L‐rGO counter electrode exhibited an energy conversion efficiency ( η ) of about 1.8%. It also displayed an excellent mechanical stability and durability after bending for 1000 cycles at a small curvature radius of 10 mm. The high flexibility, low cost and efficient catalytic activity make ST‐PEDOT:PSS/L‐rGO composite films promising counter electrodes for flexible DSSCs. Abstract : Dye sensitized solar cell with a TiO2 nanotube/Ti mesh photoanode and a sulfuric acid‐treated poly(3, 4‐ ethylenedioxythiophene):poly(styrenesulfonate)/less‐defective reduced graphene oxide composite film counter electrode displayed an excellent mechanical stability and bending durability.